TRANSFER PRICES IN ROMANIAN ECONOMY - ANDREEA-LAVINIA CAZACU (NEAMTU) (Annals of the University of Petrosani: Economics, 2016)
Transfer prices are a delicate subject and of major importance in jurisdictions to which they belong, as they are often used as a means of exploiting tax legislation. In proceedings of tax inspection and financial control carried out by the tax authorities, a special place is occupied by the transactions between affiliated entities with Romanian companies. The purpose of the tax inspection is: combating tax evasion and tracking these transactions to be carried out at market prices. The article aims to present how transfer prices affect the value of an enterprise, but also the methodological aspects relating to tax inspection and the necessary documents in order to deciphering the mode of transfer pricing in Romania.